The Most Prestigious Research Areas in Financial Economics From 1896 to 2006: Scientometrics Based on Complex Networks - Passos, Marcelo De Oliveira; Gonçalves, Jéssica Rodrigues; Tessmann, Mathas Schneid; Pereira Uhr, Daniel De Abreu; Pinto, Alex Cerqueira (International Journal of Accounting and Financial Reporting, 2024)
This work has three objectives related to scientometrics of financial economics from 1896 to 2006: (i) to detect which are the most cited authors and co-authors of a sample of the most influential works in the finance literature; and (ii) define the most relevant co-authorship groups in this sample; and (iii) develop a complex network with the links between these clusters, authors and co-authors. We used the Complex Network Statistics weighted degree metric, IDEAS/RePEc scores, and ranking to achieve the first objective. For the second, we adopt the modularity class process. For the third, we use Yifan Hu's proportional layout algorithm. The database was gathered from two sources, the Institute for New Economic Thinking's The History of Economic Thinking website and the references described by financial historian Peter L. Bernstein in his seminal book tracing the history of financial and economic thought.